The Persecution of Rohingya Muslims and the Path to Democratization in Myanmar - Wildan, Muhammad (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2021)
Rohingya Muslims in Myanmar have long endured severe discrimination and persecution. Although the Rohingya have lived in Myanmar for centuries, their existence is not fully accepted by the majority of Buddhist society. Rohingya Muslims residing in the north-western area of Rakhine are considered stateless people. In the last ten years, Rohingya Muslims have been treated severely and even expelled from their place of birth. This humanitarian crisis has attracted many international organizations that are aiding Rohingya and urging Myanmar’s civilian government to recognize Rohingya as an official ethnic group. This article explores the roots of Islamophobia in Myanmar and analyses its effect on Muslims’ daily life in Myanmar, and in particular for the Rohingya. Ultimately, it is important to discern the path of democratization in Myanmar, as currently led by Aung San Suu Kyi’s National League for Democracy (NLD), analyzing the present state and future of democratization of the country, especially on a socio-political level.